Does sustainability pay off for Sharia companies? Unveilling the nexus between sustainability performance and firm value - Asyof, Rifqi Aqil (Journal of Islamic Economic Insights, 2025)
This study aims to analyze the influence of sustainability on the firm value of Sharia-compliant companies in Indonesia. Panel data regression with a fixed effect model is employed to address this objective. The research findings suggest that sustainability aspects do not significantly affect firm value for several reasons, including a lack of understanding, obstacles during the translation process, uncertainty in the regulatory framework for sustainability projects in Indonesia, and the absence of evident financial rewards for sustainability efforts. Based on these findings, policymakers should proactively encourage the implementation of sustainable practices among Sharia-compliant enterprises in Indonesia. Specifically, education and training programs should be designed to increase the knowledge and comprehension of sustainability principles among corporate executives and staff.